Adult Education through Multiple Method For Poor Rural Illiterate Women in Indonesia - Kamin Sumardi (Intelektual Pustaka Media Utama, 2012)
ABSTRACT This Study is aimed at producing basic literacy learning model which effective and accountable. Fact has also shown that the implementation of literacy teaching is to combines comprising REFLECT (Regenerated Frerian Literacy through Empowering Community Techniques), LEA (Language Experience Approach) and PRA (Participatory Rural Appraisal). This study employs research and development as the methods. The data are collected through observation, interview, and test. The subjects are illiterate women in West Java, Indonesia. The results: 1) the learners have had awareness in learning, understood the meaning and the benefit of the learning regarding reading, writing and numerical problems; 2) the learners need to learn that can involve them in their daily activity; 3) supports are acquired from society, religion, youth and woman figures; 4) learning of literacy with multiple methods can synergize learners, the potential and daily activity of learners, the exploration of natural potential and its use in the life. The conclusion was effective in learning reading, writing, numerical problems and can be applied in the life of the learners.